10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
BACKGROUND: Quality improvement aims to systematically devise solutions to complex issues and problems in services and systems. However, many quality improvement initiatives aim to address outcomes rooted in historical policy and practice, where organisational memory may be long lost. A solid foundational understanding of past practice and policy is important to contextualise the present and highlight previous changes with sustained impact. However, it can also help to show deteriorating performance, and suggest potential proven interventions which may be suitable to re-explore. and identify areas which remain unchanged and problematic over the years, despite the best efforts of healthcare staff, leaders and policymakers, indicating where deeper systemic and cultural change is required beyond the quality improvement approach. METHODS: This paper introduces a tool and approach, the Historically-Informed Quality Improvement matrix (HIQI) for mapping evidence around contemporary healthcare service quality against historical data on the same services, to identify key areas for policy retention, intervention evaluation, quality improvement and cultural change. The paper illustrates the tool's use through a worked example of Black (African, African-Caribbean and Mixed) ethnic minority women's experiences in maternity care amid a backdrop of inequalities in maternity outcomes. Ten oral history interviews with Black women who used local hospital trust maternity services 1984-2004 were conducted, alongside focus groups with 11 Black women who had used the same services in the past 12 months. RESULTS: In the worked example, using the HIQI tool identified friendly and caring midwives were the heart of a positive birth experience; improvements in satisfaction were evident resulting from proactive hiring of midwives from similar racial/ethnic groups to mothers, and increased attention to maternal mental health. However, connection to staff and time between appointments had deteriorated over the years and women had less confidence in what to expect in pregnancy. Issues around racial and unconscious bias and lack of voice were a prominent theme across the years, suggesting these are deep-seated issues that require broader institutional and societal cultural change and are unreliable targets for quality improvement approaches. Three quality-improvement projects for the hospital trust were identified through use of the HIQI tool. CONCLUSION: The HIQI approach detailed in this paper enables quality improvement practitioners to develop a richer understanding of changes to services over the years, and develop evidence-based plans for quality improvement and service evaluation. The approach also highlights core issues which are deep-seated issues within the institution requiring a comprehensive culture change strategy alongside quality improvement efforts.